2018
DOI: 10.3989/gya.1103172
|View full text |Cite
|
Sign up to set email alerts
|

Lipase-catalyzed transesterification of epoxidized soybean oil to prepare epoxy methyl esters

Abstract: SUMMARY:Epoxidized soybean oil methyl esters could be efficiently prepared with the transesterification of epoxidized soybean oil (ESBO) with a lower dosage of methanol using lipase Novozym 435 as catalyst. The optimum parameters were as follows: the molar ratio of 5:1 (methanol to ESBO), 5% Novozym 435 as catalyst, at 45 °C for 14 h, with a stirring speed of 600rpm, under which the epoxidized soybean oil methyl esters (ESBOME) could be obtained at a 95.7% yield. During the enzymatic transesterification proces… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 33 publications
3
7
0
Order By: Relevance
“…Liu and Duan reported that Novozym 435 can be recycled using filtration, which was also demonstrated up to three cycles in this work. The catalytic activity of the enzyme in 2M2B remained high with a rising number of cycles.…”
Section: Resultssupporting
confidence: 62%
“…Liu and Duan reported that Novozym 435 can be recycled using filtration, which was also demonstrated up to three cycles in this work. The catalytic activity of the enzyme in 2M2B remained high with a rising number of cycles.…”
Section: Resultssupporting
confidence: 62%
“…300 The transesterification of epoxidized soybean oil catalyzed by N435 permitted the production of epoxidized soybean oil methyl esters with a 95.7% yield. 301 The biocatalyst was reutilized in 10 cycles maintaining the activity. Vinyl acetate and 2-phenethyl alcohol have been used to produce 2-phenylethyl acetate in hexane employing N435 as a catalyst.…”
Section: Lewatit Vp Oc 1600mentioning
confidence: 99%
“…At least on the tube scale, it is likely that, in the case of Novozym 435 ® , the costs associated with the immobilization might be fully compensated [ 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 ]. Indeed, the formulation can be recycled, using filtration, for sometimes up to 10 cycles, as a report from Liu et al demonstrates [ 49 ]. It is also important to remember that in such a bead-adsorbed enzyme formulation, the non-catalytic ballast of the carrier represents a tremendous portion of the biocatalyst’s mass (90 to >99 wt.%) [ 37 , 50 ].…”
Section: Discussionmentioning
confidence: 99%